2002
DOI: 10.1139/v01-200
|View full text |Cite
|
Sign up to set email alerts
|

2001 Lemieux Award Lecture Organic chemistry and hemoglobin: Benefits from controlled alteration

Abstract: Hemoglobin carries oxygen in circulation within red cells but does not function outside the cells because it fails not only to release oxygen but also dissociates into dimers that make up the tetrameric protein. Bifunctional anionic acylating agents that contain a structurally rigid bridge introduce cross-links that stabilize hemoglobin and alter its oxygen affinity so that it could be used to carry oxygen outside cells. Nitric oxide binds to hemoglobin and in circulation this causes undesirable increases in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The bis-tetramers are possible alternatives to nonspecifically linked oligomers in red cell substitutes. Research with PEG-Hb's has shown that an increase in the overall size of the species results in prolonged circulation life and minimizes increases in mean arterial blood pressure. , In addition, the bis-tetramers are good candidates for studying the relationship of structure to function in oxygen carriers. , The idea that cross-linked bis-tetramers might be less vasoactive in circulation than cross-linked tetramers derives from analyses of heterogeneously cross-linked hemoglobins that have been used in clinical trials. The oxygen-binding properties of the individual species in such mixtures have not been determined, whereas those of the purified cross-linked tetramers in other trials have been measured . Our studies reveal that cross-linked bis-tetramers have higher oxygen affinities and decreased cooperativity compared to the clinically tested mono-tetramers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The bis-tetramers are possible alternatives to nonspecifically linked oligomers in red cell substitutes. Research with PEG-Hb's has shown that an increase in the overall size of the species results in prolonged circulation life and minimizes increases in mean arterial blood pressure. , In addition, the bis-tetramers are good candidates for studying the relationship of structure to function in oxygen carriers. , The idea that cross-linked bis-tetramers might be less vasoactive in circulation than cross-linked tetramers derives from analyses of heterogeneously cross-linked hemoglobins that have been used in clinical trials. The oxygen-binding properties of the individual species in such mixtures have not been determined, whereas those of the purified cross-linked tetramers in other trials have been measured . Our studies reveal that cross-linked bis-tetramers have higher oxygen affinities and decreased cooperativity compared to the clinically tested mono-tetramers.…”
Section: Discussionmentioning
confidence: 99%
“…In cases where oxygen-binding properties of red cell substitutes had been rationally produced, cooperative, low oxygen affinity species were sought to maximize oxygen delivery …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Before these results were known, cross‐linking reagents were engineered to target specific amino acid residues on the Hb molecule 31–33. In 2001, Kluger34 asked, “Can hemoglobin be chemically altered so that it can effectively deliver oxygen and remain in circulation outside the red cell?”. Kluger's group thus began their efforts to selectively introduce crosslinks in the cationic amino group regions of the Hb molecule.…”
Section: Site‐specific Hboc Designmentioning
confidence: 99%